The Determinants of Innovative Work Behavior in Knowledge Intensive Business Services Among Knowledge Workers in Malaysia - Yeoh, Khar Kheng (2012)
The foundation of innovation is ideas and it is the individual worker in an organization who “develops, carry, react to, and modify ideas”. Innovative work behavior has a central role in the long–term survival of knowledge-intensive business services in Malaysia. The study that seeks out the determinants of knowledge worker’s innovative work behavior is critical for a better understanding of how organizations in KIBS can best manage the level of innovative behavior of the knowledge workers. Therefore, this study attempts to synthesize all the three independent variables of leader-member exchange (LMX), pro-innovation organizational climate and social capital, and delineate their relationship onto the dependent variable of innovative work behavior of knowledge workers. In addition, all independent variables and dependent variable are theoretically underpinned by the Social Exchange Theory (SET) in view of the paradigm that innovative work behavior is a social process as proposed by Blau. A quantitative method was utilized and data were collected using mail survey. A total of 1520 questionnaires were distributed and 310 deemed usable for analysis using SPSS, resulted in 20.6 % response rate. The results revealed that there were significant relationship between pro-innovation climate, social capital and leader-member exchange with innovative work behavior of knowledge workers. In addition, among the three independent variables, pro-innovation climate had been found to be the most significant predictor of innovative work behavior; followed by social capital and leader-member exchange. This study contributes in highlighting the important determinants related to knowledge workers’ innovative work behavior in knowledge-intensive business services (KIBS). Moreover, firms in KIBS can strategically manage these variables to further enhance the productivity of the knowledge workers in Malaysia.